The philosopher in the city : the moral dimensions of urban politics - Arkes, Hadley (Princeton legacy library, 1981)
After reestablishing the connection between morality and the law, the author develops a coherent position on many of the most controversial issues of urban life: the political uses of the streets; verbal assaults and the defamation of racial groups; the legitimate restriction of public speech; segregation, busing, and the use of racial quotas; education, housing, and the problem of the ghetto"; prostitution, gambling, and the "regulation of vices."Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905